Protective effects of d-limonene and linalool on female rats intoxicated with 7,12 dime-thylbenz(a)anthracene (DMBA) - Tanyildizi, S.; Servi, K.; Ciftci, O. (My University, 2009)
This study was carried out to investigate the potential antioxidant effects of 2 monoterpenes, linalool and d-limonene, in female rats orally treated or not with dimethylbenz(a)anthracene (DMBA). For this purpose, 70 female Wistar Albino rats (7-8 weeks old) were randomly divided into l0 equal groups according to the modalities of monoterpene dietary supplementation and/or oral DMBA (65 mg/kg) treatment. Negative controls were not supplemented and untreated, positive controls received only DMBA, whereas all the other groups were fed with diets enriched by 5% limonene or linalool for 150 days and received no DMBA (groups 2 and 3) or DMBA administration 15 days after (groups 5 and 6), in the same time (groups 7 and 8) or 6 days before (groups 9 and l0) the beginning of terpene supplementation. Plasma concentrations of MDA (considered as a marker of oxidative stress) were measured in all animals on days 15,30,45,60,75 and 150. This marker was dramatically increased by DMBA treatment alone then gradually declined. By contrast, the dietary monoterpene supplementation has induced significant decreases of spontaneous MDA formation and also has markedly inhibited DMBA-induced lipid peroxidation, the best protocol being initiation of supplementation before DMBA administration. Furthermore, linalool has appeared as a more potent antioxidant than limonene. These results evidence the protective in vivo effects of monoterpenes on an experimentally induced oxidative stress and suggest that dietary supplementation would be beneficial for the prevention of free radical damage.
Keywords: Anti-oxidant; D-limonene; Dietary supplementation; Dimethylbenz(a)anthracene; Linalool; Malondialdehyde; Rat